Fatigue strength of tungsten inert gas-repaired weld joints in airplane critical structures - Nascimento, Marcelino P. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Payao Filho, Joao da C. (Elsevier B.V. Sa, 2011)
In this work the effect of Gas Tungsten Arc Welding (GTAW) repairs on the axial fatigue strength of an AISI 4130 steel welded joint used in airframe critical to the flight-safety was investigated. Fatigue tests were performed at room temperature on 0.89 mm thick hot-rolled plates with constant amplitude and load ratio of R = 0.1, at 20 Hz frequency. Monotonic tensile tests, optical metallography and microhardness, residual stress and weld geometric factors measurements were also performed. The fatigue strength decreased with the number of GTAW repairs, and was related to microstructural and microhardness changes, as well as residual stress field and weld profile geometry factors, which gave origin to high stress concentration at the weld toe. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: AISI 4130 aeronautical steel; Repair welding; Weld metal and HAZ; Microstructure; Weld geometry; Flight-safety